Analysis of the whole main structure morphological evolution and velocity distribution characteristics of a high-pressure water jet by an imaging experiment. (15th June 2023) - Jiang, Mingjun; Wang, Fengchao; Yuan, Man; Liu, Yingke; Xiong, Ji; Niu, Yue; Long, Zhaoxi
Highlights: The state of a continuous waterjet has been meticulously captured. Evolution of the jet morphology was analyzed and described. A new classification of jet structure was proposed. Velocity characteristics of water jet was analyzed. Comprehensive analysis of the high-efficiency jet impact radius was performed. Abstract: Water jets play a crucial role in physically-fluidized coal mining. Analyzing the whole morphology and velocity characteristics of water jets is essential for the improvement of coal-breaking efficiency. An imaging experiment was performed to capture the intricate geometrical features of the water clusters and droplets at diverse distances from the exit of the nozzle. Based on the obtained results, a new classification of the jet structures has been proposed. Additionally, the axial of the jet velocity was predominantly characterized by a piecewise linear decreasing. For the coal-breaking efficiency of long-distance jets, the velocity could not be a major concern because the velocity attenuation is minimal. In contrast, the form of the jet is crucial for improvement. An empirical model of the high-efficiency jet impact radius was established, leading to the introduction of the concepts of critical, optimal, and farthest jet target distance, which will inform future research on high-efficiency coal-breaking.